PEMETAAN POLA SEBARAN TOTAL SUSPENDED SOLID (TSS) DI PERAIRAN TELUK SEMARANG MENGGUNAKAN CITRA SATELIT LANDSAT 7 ETM DAN LANDSAT 8 - sigit febrianto; Nurul Latifah (Jurnal Harpodon Borneo, 2017)
Semarang Bay is the waters that become the place of 5 watershed that will bring suspended solid material into the waters. TSS that enter the water will affect the life of aquatic organisms this is because it can affect the penetration of light and breathing of aquatic animals. This study aims to determine the concentration of TSS in Semarang Bay, to know the status of water pollution based on TSS variable and to know the cause of the increase of TSS. Landsat satellite imagery 8 can be used to estimate TSS concentration using TSS = 0,6432 * (ETM1 + ETM3) / 2-5,9063 algorithm. Based on the result of spatial analysis it is known that there is an increase of TSS concentration from 0,2-158,1 mg / L in 2013 to 0-250 mg / L in 2017. While the concentration is also followed by increasing its extent from 2003 to 2007. Based on result The concentration of TSS is known that the waters of Semarang Bay are categorized as medium contaminated. Keywords: Total Suspended Solid, Semarang Bay, Landsat 8 dan 7 ETM.